Physical activity, undernutrition and child development - Meeks Gardner, J. M.; Grantham-McGregor, S. M. (The University of the West Indies, Mona, Jamaica, 1994)
Although evidence is accumulating which suggests a casual relationship between under-nutrition and poor development in young children (Simeon & Grantham-McGregor, 1990; Pollitt et al. 1993), the mechanism linking the two remains unclear. One hypothesis is that lack of dietary energy leads to reduced activity levels, which in turn leads to reduced exploration and subsequently results in developmental delays (Levitsky, 1979). This is known as the ‘functional isolation hypothesis’. In the present review we will discuss the evidence for this hypothesis in young children as it relates to activity levels.
Keywords: under-nutrition; poor development; child development; physical activity